Determining the Effect of Process Innovation on Financial Performance of Deposit Taking Saving and Credit Cooperative Societies in Laikipia County, Kenya - Jillo, Safia Abdi; Kanyiri, Adel; Moguche, Abel (International Journal of Finance, 2023)
Purpose: To determine the effect of process innovation on financial performance of deposit taking saving and credit cooperative societies in Laikipia County, Kenya Methodology: The study used descriptive research design to collect data from nine deposit taking Saccos in Laikipia County. Specifically, the target population were 118 respondents who included 22 departmental managers and 96 support staff selected using census method. Notably, the study collected both primary and secondary data whereby primary data was collected in form of questionnaires from departmental managers and support staff. Secondary data was collected from financial reports such as income statement, whereby various financial ratios such as return on assets, return on equity, gross profit, net profit, liquidity ratio were noted. Further, the study conducted a pilot study in Bingwa Sacco in Kirinyaga County whose managing director, 3 departmental managers and 13 technical staff took part. The study also measured reliability using Cronbach Alpha Coefficient method while face, content and construct types of validity were measured. Further, SPSS software version 24 was used to analyze and generate various statistical reports whereby, in the analysis of the questionnaire, the study examined and generated descriptive statistics such as frequency, percentage and mean. Additionally, the study generated various linear regression statistics such as model summary and ANOVA of each independent variable. Thereafter the study generated inferential statistics to test the general model. Results: The results indicated that 92(82%) strongly agreed and 16(14%) agreed on a mean of 4.75, that there were effective complaint management processes which clients used in case of dissatisfaction. Further, 74(67%) strongly agreed and 17(15%) agreed on a mean of 4.23 that cheque clearance took less time since the system was able to process it faster. That notwithstanding, 74(67%) strongly disagreed and 21(19%) disagreed on a mean of 2.23, the Sacco management had invested a lot in equipping the Sacco with good working computerized systems. In addition, 65(58%) strongly disagreed and 31(28%) disagreed on a mean of 2.29, that the Sacco had established updated system checks to facilitate less downtime during financial transactions. Additionally, R was 0.864 while R-square was 0.747 at a Durbin Watson of 1.601. This meant that process innovation predicted 74.7% on financial performance which was positively correlated d at 1.601. Further, the p-value was 0.022 which was below than 0.05 and therefore, the study rejected null hypothesis. Unique contribution to theory, policy and practice: The study concluded that Sacco's bid to incorporate ICT to assist in financial transaction such as having enough servers and skilled staff was still low hence increased system downtimes. Consistent downtime exposed the client deposits to cyber theft since the hackers noted this weakness and used to their advantage to commit crime. Therefore, the Sacco management should invest in secure servers to protect client's information from unauthorized access or use. This could also involve wither hiring new ICT personnel or sharpening the skills of the current ICT staff through training and development. Additionally, the Sacco staff should maintain a strict policy of ensuring that they do not issue passwords to anyone or leave their computers logged in in their absence even when there is a system failure to reduce cyber hacking. Further, the Sacco ICT management should expand their domains to ensure that there are minimal system failures to facilitate smooth flow of operations